Analisis Kandungan Klorofil pada Benih Padi Tua (Oryza Sativa L.) yang Terpapar Medan Magnet Extremely Low Frequency (ELF) pada Masa Pertumbuhan Vegetatif - Saputra, Agong; Listiana, Ika; Saputri, Dwijowati Asih (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate the effect of Extremely Low Frequency (ELF) magnetic field exposure on chlorophyll content in aged rice (Oryza sativa L.) seeds during the vegetative phase. Chlorophyll is the primary pigment in photosynthesis, playing a crucial role in light absorption and the conversion of energy into organic matter essential for plant growth. The research method used was a completely randomized design (CRD) with ELF magnetic field exposure treatments at an intensity of 0.2 mT for 3 minutes 54 seconds, 7 minutes 48 seconds, 11 minutes 42 seconds, and a control treatment without exposure. The results showed that (1) ELF magnetic field exposure for 11 minutes 42 seconds produced the highest chlorophyll a, chlorophyll b, and total chlorophyll content compared to other treatments. (2) The control treatment (P0) resulted in lower chlorophyll a, chlorophyll b, and total chlorophyll content than the P1, P2, and P3 treatments. (3) Longer exposure durations, such as in the P3 treatment, were proven to significantly increase chlorophyll content, potentially optimizing the photosynthesis process in rice plants.